Contemporary Africa challenges and opportunities - edited by Toyin Falola (New York Palgrave Macmillan, 2014)
The challenges facing Africa today have changed little since the end of colonial rule. Once the optimism that characterized the African struggle for independence dissipated in the 1960s, statesmen of the continent's respective nations were quick to realize how many unsettling issues had developed during the period of European colonial rule. For the most part, these new statesmen focused so much on retaining their political power that they focused little attention and resources to the socioeconomic welfare of their subjects. As a consequence, sixty years after independence, African nations still find it difficult to face a number of challenges: to establish meaningful democratic-governing institutions that could permanently eradicate graft, unwarranted patronage and corruption; to configure self-reliant economies capable of redressing the poverty gap and adapt to the developmental needs of the people of the continent; and to establish concrete social structures centered on the advancement of gender equality, the protection of women's rights, and the promotion of education and healthcare. Many researchers and policy analysts have emphasized the consequences of bad political leadership on the continent, limiting the discussion to one about power and the powerful. This volume shifts the focus to the plight of the powerless, poor, and destitute millions on the continent who continue to search for opportunities despite the accumulated negatives of bad colonial, political, and economic policies. For these millions, the day-to-day challenges of dealing with the negative effects of debt-ridden and corrupt societies, diseases such as HIV/AIDS, population growth and poor family planning, ineffective attention to human and environmental rights issues, and the flight of many of their brightest sons and daughters remain their plight. The collection's strength lies in its approach to contemporary African challenges with a twenty-first-century framework?namely, the UN's Millennium Development Goals (MDG)?while also presenting important issues from various African perspectives. Unlike the pessimistic emphasis on corruption and conflict articulated by many scholars, the studies gathered here constitute a more balanced view of African agency, both positive and negative, in the face of global pressures.
Includes bibliographical references and index.
Keywords: Poverty--Africa.